PENINGKATAN KEMAMPUAN KEAKSARAAN ANAK MELALUI PERMAINAN PETAK UMPET HURUF DI RA TARBIYATUS SIBYAN PLOSO KARANGTENGAH DEMAK - Aulina Fitriya; Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2024)
Children's literacy abilities have not yet developed according to expectations when learning, one way or step that is believed to improve children's literacy is through playing hide and seek with letters. The formulation of the problem in this research is how to implement learning and improve the literacy skills of RA Tarbiyatussibyan Ploso Karangtengah Demak children. The Classroom Action Research method uses data collection techniques using observation, interviews, performance assessment and documentation techniques. The subjects were students from group A RA Tarbiyatussibyan, with a total of 15 children consisting of 10 boys and 5 girls. The aim is to determine the implementation and improvement of children's literacy skills through the letter hide and seek game at RA Tarbiyatussibyan. The results of this research show that: (1) the implementation of literacy learning for the children of RA Tarbiyatussibyan Ploso Karangtengah Demak in stages: a) Providing motivation at each meeting before the children learn to know literacy is carried out in various ways, the purpose of which is to ensure that the children are always enthusiastic about learning. b) Researchers always carry out good apperception by reading the letters of the alphabet to see the child's ability to recognize letters. c) The style of delivering material used by researchers varies every day, even though the material presented remains the same; (2) increasing children's literacy skills through the game of hide and seek letters can be seen from observations at the beginning of the research before the action was implemented, where the percentage of success only reached 42%. The percentage of children's success in cycle I increased to 65% and the research was stopped in cycle II because the children's success had reached the predetermined average value, namely 82%.